Design and transient experimental analysis of a pulsed brushless doubly fed alternator in a capacitor charge power supply system. Issue 1 (9th November 2021) - Yu, Kexun; Zhao, Tantan; Xie, Xianfei; Guo, Songlin
Abstract: There is an urgent need to develop a robust capacitor charge power supply (CCPS) system to meet the requirement of pulsed load in all‐weather mobile occasions such as vehicle, ship and aircraft. Brushless doubly fed alternator (BDFA) works through the rotor's pole pairs' transformation to get excitation indirectly, without magnets, brushes and slip rings. Both DC and AC excitation can be used. Therefore, it has high reliability and a good application prospect in the CCPS system. However, the existing research studies lack analysis of the parameters that affect charging performance, and have no experimental analysis of the prototype. To solve this problem, a comprehensive design method and experimental procedure of the pulsed BDFA are proposed and investigated. First, the operation principle of the pulsed BDFA is illustrated. Then, the charging performances under different design schemes are comparatively analysed through the finite element analysis (FEA). Finally, a prototype of the pulsed BDFA is manufactured, and the related experiments are carried out. The results verify the feasibility of the experimental procedure and the accuracy of FEA. The comprehensive design method and experimental procedure in this work provide a straightforward reference for the subsequent applications in the CCPS system.